COMBINED VOLATILITY AND MARKOV SWITCHING MODELS FOR CURRENCY CRISIS DETECTION IN INDONESIA ON REAL DEPOSIT RATE INDICATORS - Widyantara Arya Bagja Soenardi; Sugiyanto Sugiyanto; Winita Sulandari (International Conference on Economic Business and Social Science, 2023)
Indonesia experienced its worst currency crisis in the mid-1997 and the global currency crisis in 2008. The impact of these crises had a significant negative effect on the country's economy. Therefore, a system is needed to detect currency crises and prevent their recurrence. One indicator that can be used to detect currency crises is real interest rate savings. A combination of volatility models with Markov switching can be used to detect currency crises. The research results showed that the MS-ARCH(1) model can be used to detect crises in real interest rate savings indicators. Based on these results, it is predicted that the Indonesian economy will remain stable from mid-2022 to 2023